Food waste from a university campus in the Middle East: Drivers, composition, and resource recovery potential. (October 2019) - Abdelaal, Ali H.; McKay, Gordon; Mackey, Hamish R.
Graphical abstract: Highlights: First food waste study at a university campus in Qatar. Mixture of large-scale catering services and specialized franchise food outlets. The per person food waste generation exceeds the highest globally reported rates. Overproduction is the main driver for food wastage resulting from food display. Highlights the possible scale of issue at cafeterias and need for caterer education. Abstract: Food waste is a pressing issue that imposes economic, social and environmental impacts on both developing and developed countries. This study analyzes quantitatively and qualitatively the generated food waste at various food outlets of a university campus in Qatar. It is a fundamental step to manage the issue of food waste from educational institutes. The investigation comprised four stages: screening, sampling, surveying, and synthesis. Food waste generation at the sampled locations was estimated at 329.5 kg/day or 80 t/year. Based on per sales estimates, total food waste was 980 g/sale and 757 g/sale at the student male and female housing complexes, respectively, equating to roughly one wasted meal for each sold meal. The majority of this waste was avoidable waste and the root cause for the excessive food waste generation was overproduction rather than consumer wastage. The study found that the main food provider, who primarily serves buffet style meals, lacks the proper tools to measure food waste generated at their cafeterias. Past experience was the primary tool to support the company's demand management estimation which has proven unsuccessful and highlights the need to not only educate the consumer but also food providers. Possible treatments routes are discussed based on food waste characterization findings.